A Survey for Research Literature Review of the Origin, Spread and Variation of the Chinese Folk Song “Jasmine Flower” - Liang Tao; Jacqueline Pugh-Kitingan; Lee Chie Tsang Isaiah (Atlantis Press, 2023)
Jasmine Flower is a well-known Chinese Han folk song that holds significant historical and cultural importance in China and beyond. Its influence extends to the realm of world music as well. Chinese academic circles began to study the Chinese traditional folk song Jasmine Flower around the 1980s. The main disputes about this folk song are the region of origin and the attribution of various variants. It briefly introduces some basic research done since the 1980s, some about the origins, variations of Jasmine Flower, and relevant several important researchers. The discussion emphasizes some of the main researchers and their work over the years, especially in the fields and history sources of anthropology, linguistics and ethnomusicology.